The puzzling evolution of the home bias, information processing and financial openness - Jordi Mondria; Thomas Wu (University of California, Santa Cruz Institute for International Economics (SCIIE), 2007)
This paper presents a rational expectations model of asset prices with rationally inattentive investors that, unlike previous papers, explains both the substantial amount of equity wealth invested domestically and the puzzling time series behavior of the home bias - an initial plateau before 1985, then a decrease until 1994 followed by stabilization on another plateau. When there is a financial liberalization as in developed countries during the 80s, investors exploit past information to predict current asset payoþs. The resulting endogenous local information advantage generates a gradual decrease of the home bias until its steady state. In the long run, the home bias remains large due to the interaction of the optimal attention allocation with the optimal portfolio choice. Using measures of information capacity and .nancial openness as explanatory variables, we are able to explain at least 46.8% of the variation of the home bias for 19 developed countries from 1988 until 2004. Our estimates show that both variables are signi.cant, with home bias decreasing with .nancial openness and increasing with information capacity, as predicted by our model.
Keywords: F30; G15; D82; G11; 330; home bias; rational inattention; asymmetric information; portfolio choice; Home Bias Puzzle; Portfolio-Management; Portfolio-Investition; Rationale Erwartung; Asymmetrische Information; Theorie; Schätzung; Industriestaaten